The ca. 1.8 Ga mantle plume related magmatism of the central part of the Ukrainian shield. (2nd January 2016) - Shumlyanskyy, Leonid; Mitrokhin, Oleksandr; Billström, Kjell; Ernst, Richard; Vishnevska, Eugenia; Tsymbal, Stepan; Cuney, Michel; Soesoo, Alvar
Abstract: Palaeoproterozoic (ca. 1.8 Ga) mafic and ultramafic dykes are widely distributed within the whole Sarmatian segment of the East-European craton. This paper focuses on new geochronological, geochemical and isotope data obtained for mafic and ultramafic dykes of the Ingul terrain. Geochronological data available for these dykes indicate ages around 1800 Ma. We provide a new U–Pb zircon age of 1810 ± 15 Ma obtained for a dolerite dyke in the Kirovograd area. Geochemical and petrographical data allow identification of three groups of dykes: (1) kimberlites, (2) high-Mg# subalkaline rocks (picrite, camptonite, subalkaline dolerite etc.) and (3) tholeiite dolerite. Rocks of these groups were probably derived from different sources. εNd1800 values of studied rocks vary from 0.7 to 2.8. The highest values were obtained for mantle xenoliths and their kimberlite host (εNd1800 = 2.5–2.8). Rb–Sr data yield a regression age of 1729 ± 20 Ma with an initial 87 Sr/ 86 Sr = 0.70366 ± 41 (MSWD = 10.8). The whole-rock lead isotope data scatter, but data for sub-groups of samples can tentatively be fitted to parallel 1.8 Ga isochrons. The geochemical data indicate rocks to have formed by partial melting and the degree of melting is thought to be a function of formation depth, the latter ranging from sub-lithospheric to lower-crustal levels; we assume that melting was caused by a mantle plume. Dyking in the Ingul terrain was closely associated in time and space with metasomatic albitites that host numerous economic U deposits.